ASSOCIATION BETWEEN HEART RATE VARIABILITY AND BLOOD PRESSURE IN ELDERLY WORKER - Kartika, Ronald Winardi; Susanti, Yosephin Sri; Winata, Susanti Dewi (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2024)
Life expectancy increases along with improving health. A good healthy life as an impact that there are still many workers in old age who are still needed. The effect of age and work environment will affect the normal range of time-domain heart rate variability (HRV) in older worker. Heart rate variability test might detect autonomic nervous system influenced by blood pressure level, stress, and working environment. A low HRV value is considered an independent marker of risk of death. However, age-related decline in HRV may limit its predictive value, especially in older workers. It was found that the decrease in HRV decreased with age and length of service. The elevation of HRV at specific wavelengths was correlated with the blood pressure values of hypertension patients; however, in the uncontrolled hypertensive group, the values of SDNN, SDANN, ASDNN, VLF, LF (indicating sympathovagal balance), and HF were significantly lower.